Improves Children's Ability In Learning To Read And Write Through The RERIRO Method For Slow Learners - Apryani, Dwi Surami; Listiowati, Martiana Putri; Husna, Maulida Fitria; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
This study aims to determine whether the use of the RERIRO method can improve reading and writing skills in Slow Learners at SD N Keditan. This research was carried out in one of the classes of SD N Keditan, namely class IV and apply experiments using thepaper roll game Researcher's suggested that the RERIRO method can be used in teaching to improve reading and writing skills in children with slow learner. The results of the study indicate that there is an increase in the results of children in reading and writing.Elementary school teachers to using the RERIRO method as a bridge in teaching reading and writing, especially in Indonesian subjects.It can make students more interested in learning activities that are being carried out.